EFFECTIVENESS OF HAEMORRHOIDAL ARTERY LIGATION VIA PALPATORY - Shabbir, Hassan; Majeed, Farhan Ahmed; Raza, Ahmed; Bashir, Umar; Cheema, Mohsin Saleem; Shabbir, Ayema; Khan, Saad-Ur-Rehman (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the effectiveness of the haemorrhoidal artery ligation via palpatory method among patients with grade II and III hemorrhoids.Study Design: Observational prospective study.Place and Duration of Study: The study was conducted at Combined Military Hospital Multan where with hemorrhoids were operated between May to Nov2018.Methodology: A total of 121 patients participated in this study. Patients included in the study were aged between 20-60 years of age with grade II and III hemorrhoids. Patients were selected from out-patient department. They were explained the purpose of the study and those who consented to participate in the study were enrolled through a written consent form. Digital rectal examination was done under spinal anesthesia followed by proctoscopy and hemorrhoids were identified. Split proctoscope was passed and hemorrhoids were isolated one by one. Haemorrhoidal artery was palpated sutured with vicral 3/0. Follow up at 3weeks and 8 weeks.Results: Male respondents accounted for 50 (41.3%) whereas their female counterparts comprised 71 (58.7%). The mean age of the male and female respondents was 43.76 ± 10.08 and 44.52 ± 10.59 years respectively. Out of 121 patients that underwent haemorrhoidal artery ligation, only 33 (27.3%) had post-operative complications. Most of the patients had rectal bleeding followed by post-operative defecation pain, anal fissure, fistula in ano and recurrence. Conclusion: In conclusion, palpatory method is painless, less invasive, has less complications and is safe alternative to open hemorrhoidectomy where Doppler guided haemorrhoidal ligation equipment is not available.